The Effect of Reflective Reading Model on Students’ Reading Comprehension of Recount Text - Maulida, Hanum; Hidayati, Dini; Rusmiati, Yanti (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study aimed to investigate the effect of the Reflective Reading model on eighth-grade students’ reading comprehension of recount texts at MTs Attaqwa 17 Bekasi. The background of this research is based on students’ difficulties in understanding the structure, sequence of events, and vocabulary in recount texts. The study employed a quantitative approach with a quasi-experimental design. The sample consisted of two classes selected through purposive sampling: an experimental class taught using the Reflective Reading model and a control class taught conventionally. The research instrument was a multiple-choice test administered in both pre-test and post-test. The results showed that the experimental class achieved a significantly higher post-test mean score (90.87) compared to the control class (71.07). An independent t-test revealed a significant value of < 0.001, indicating that the Reflective Reading model had a positive effect on students’ reading comprehension. These findings suggest that reflection helps students connect texts with personal experiences, enhances metacognitive awareness, and fosters critical thinking skills. Therefore, Reflective Reading is proven to be an effective alternative learning strategy for improving students’ reading comprehension in a more meaningful and contextual way.